Testosterone, Hypogonadism, and Heart Failure. (8th April 2022) - Di Lodovico, Elena; Facondo, Paolo; Delbarba, Andrea; Pezzaioli, Letizia Chiara; Maffezzoni, Filippo; Cappelli, Carlo; Ferlin, Alberto
Abstract : Male hypogonadism is defined as low circulating testosterone level associated with signs and symptoms of testosterone deficiency. Although the bidirectional link between hypogonadism and cardiovascular disease has been clarified, the association between testosterone and chronic heart failure (HF) is more controversial. Herein, we critically review published studies relating to testosterone, hypogonadism, and HF and provide practical clinical information on proper diagnosis and treatment of male hypogonadism in patients with HF. In general, published studies are extremely heterogeneous, frequently have not adhered to hypogonadism guidelines, and suffer from many intrinsic methodological inaccuracies; therefore, data provide only low-quality evidence. Nevertheless, by selecting the few methodologically robust studies, we show the prevalence of testosterone deficiency (30%–50%) and symptomatic hypogonadism (15%) in men with HF is significant. Low testosterone correlates with HF severity, New York Heart Association class, exercise functional capacity, and a worse clinical prognosis and mortality. Interventional studies on testosterone treatment in men with HF are inconclusive but do suggest beneficial effects on exercise capacity, New York Heart Association class, metabolic health, and cardiac prognosis. We suggest that clinicians should measure testosterone levels in men with HF who have symptoms of a testosterone deficiency and conditions that predispose to hypogonadism, such as obesity and diabetes. These patients—if diagnosed as hypogonadal—may benefit from the short- and long-term effects of testosterone replacement therapy, which include improvements in both cardiac prognosis and systemic outcomes. Further collaborative studies involving both cardiologists and endocrinologists are warranted.